A FEMALE WITH MALIGNANT ASCITES: A DIFFICULT CASE WITH CARCINOMA OF UNKNOWN PRIMARY - Retno W, Dyah; -, Supriono (journal of internal medicine, 2014)
Malignant ascites is the abnormal accumulation of !uid in the peritoneal cavity associated with several intra-pelvic and intra-abdominal malignancies. Among the gynecologic malignancies, ovarian carcinoma predominates. Of the gastrointestinal malignancies, ascites can occur with advanced colon, pancreas, gastric carcinoma, and esophageal carcinoma. Recent reports in the cytological literature suggest that 6% to 11% of malignant peritoneal effusions are due to tumors of unknown origin.1 We reported a 62 years old female presenting adenocarcinoma ascites, which shown confusing of site of primary origin from imaging examination. First ultrasound imaging showed mass on colon area, but re ultrasound of abdominal imaging showed the possibility of endometrium carcinoma. The CA 125 level was high (2.294 u/ml). Open laparotomy showed milliar metastatic several nodule on omental, liver, and abdominal wall. There was attachment of vesica urinaria, endometrium, colon, sigmoid, and rectum. All those result conclude this patient suffered from malignant ascites of adenocarcinoma of unknown primary origin, with highly suggestive from malignant ascites of adenocarcinoma of unknown primary origin, with highly suggestive from gynecologic malignancy that difcult to differ whether from ovarian cancer or endometrium cancer. Somehow, the epidemiology, pathophysiology, clinical presentation lead the diagnosis for ovarian cancer.
Keywords: Malignant ascites, peritonitis carcinomatous, adenocarcinoma, CA 125, ovarian cancer, endometrium cancer